Marco geológico y tectónico de la Isla del Coco y la región marítima circunvecina, Costa Rica - Rojas, Wilfredo (2012)
Geological and geotectonic framework of Isla del Coco and the marine zone off the central Pacific coast of Costa Rica. The Isla del Coco (also known as Cocos Island), in the Eastern Pacific Ocean, has a rough topography, an area of 24km2, and is the only sub-aerial topographic height of the summit of a volcano located in the margin of the Cordillera Volcánica del Coco (also known as Cocos Ridge). The Cocos Ridge is a well defined linear bathymetric height, issued from the active volcanism of the Galápagos hotspot during the last 15 million years (Ma); it is the largest geographic feature of Costa Rica, as a volcanic range of 780km long in its territorial seawaters. Isla del Coco is part of a submarine shield volcano of complex evolution, which erupted several times above sea level during the Lower Pleistocene (2.2-1.5Ma). The island and other seamounts are the result from a mantle thermal anomaly that erupted through volcano-tectonic fissures in the oceanic crust. The rocks consist mainly of alkali basaltic lava flows (aa, pahoehoe, blocky lavas) and dikes, minor trachyte lava flows, volcanic domes and dikes, with subordinate pyroclastic and epivolcanic rocks. Colluvial, soils and local littoral deposits such as sand and gravel beaches are also present. The island has a juvenile erosive stadium, but their submarine erosive arcs and platforms (90-110m and 183m depth) are probably the result of the erosion occurred during last two glacial maxima, besides slow subsidence events of the island due the thermal cooling of the volcanic shield and its oceanic crust. The most important current external geodynamic hazards are landslides, tsunamis and rare seismic events, M w ≤ 5.8 in a 300km radio associated to N-S right lateral strike slip faults. However, the limited seismic data available, and geomorphological alignments, indicates that there is some seismic activity related to local faults oriented N-S, ENE and in a lesser extend NW trend. Seismicity and rainfall have triggered landslides; liquefaction is restricted to Chatham and Wafer bays’ beaches. Moderate historical and prehistorical tsunamis were related to regional seismic events. The relative young age of Isla del Coco makes it an interesting place to study the evolution and migration of species, and their genetic features. More detailed studies related to tephrostratigraphy, neotectonics, marine geomorphology, evolution of seamounts, lava flow morphology, and submarine hydrothermal activity, are still necessary to understand the expression of internal geodynamic processes in this region. Citation: Rojas, W. & G.E. Alvarado. 2012. Marco geológico y tectónico de la Isla del Coco y la región marítima circunvecina, Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 15-32. Epub 2012 Dec 01.